Analisis Penerapan Akuntansi Pajak Penghasilan Pasal 21 Pada PT. Tri Berkat Bangsa Semarang - Yeni Kismawati; Putu Sulastri (Jurnal Akuntan Publik, 2024)
The purpose of the study is to know the calculation, cutting, reporting and recording of PPh article 21 in PT Tri Berkat Bangsa, Semarang. The data analysis of this study was done descriptively by studying, classifying, and analyzing primary data, namely records, reports and other information related to research data on PPh 21 in PT Tri Berkat Bangsa, Semarang. From the analysis on PT Tri Berkat Bangsa, Semarang in conducting PPh 21 calculations against employees remains not in accordance with the 36th tax laws of 2008 which is perfected in law no. 7 of 2021. This happens because of less precise and less following the development of applicable tax information. Thus, the cutting of PPh 21 is not in accordance with the tax law number 36 of 2008 which is perfected in law no. 7 of 2021. For the calculation of PPh 21 against employees is not permanent in accordance with applicable laws. Deposit and reporting of PPh 21 is never too late from the date under law number 36 of 2008 which is refined in law no. 7 of 2021 where the deposit of income tax article 21 of the taxpayer private person is implemented before the next 10 tax period by paying taxes owed on the salary/income earned from the company. As for the reporting before the next 20th tax period.